Translation Accuracy of Translation Shift and Method Found in Selected Ted Talk Subtitles (English into Indonesian): Translation Accuracy of Translation Shift and Method - Indriawati, Endang Dwi; Rasyid, Muhammad Nur Akbar; Syukur, Helmi (Journal of Islamic Culture and Literature (JICeL), 2023)
The purposes of this research were to figure out the Traslation accuracy of translation shift, and method found in the subtitle of the Ted Talk video English into Indonesian under the title "How to Stop Screwing Yourself Over, by Mel Robbins". The researcher uses mixed method approaches to figure out the purpose of research. It is analyzed based on three theories,  Translation Shift by Hatim (2014), Method of Translation by Vinay (2013), and Nababan et al. (2012) theory for Translation Accuracy. Meanwhile, the data was collected through questionnaires distributed to the informants. The research finding showed that the translator applies five translation shifts, seven methods of translation. There are two kinds of data in this research: affective and objective data. The affective data are from key-informants in the form of scale. Objective data are from transcript of the subttile of the Ted Talk video choosen randomly sampling in the form of words, phrases, clauses, sentences and text. The findings of this research shows that The dominant translation shift is unit shift 74, structure shift: 73, intra-system shift: 26, level shift: 18 and, class shift: 16. The dominant translation method is modulation method: 61, equivalence: 60, literal: 36, borrowing: 23, transposition: 10, calque: 1, adaptation: 1. Meanwhile, the average score for the accuracy of the translation is 2,6 out of 3. Which indicates that the translation is accurate.Keywords: Subtitle; translation accuracy; translation method; translation shift; translation quality